Effects of Rare Earth Elements on the Characteristics of,Low Temperature Plasma Nitrocarburized Martensitic Stainless Steel - Liu, R.L.; Qiao, Y.J.; Yan, M.F.; Fu, Y.D. (Journal of materials science & technology, 2012)
Low temperature plasma nitrocarburizing of 17-4PH martensitic stainless steel was conducted at 430 ℃ with and without rare earth （RE） addition. The microstructure, kinetics, microhardness, wear behavior as well as corrosion resistance of the modified layer were studied by optical microscopy, X-ray diffraction, Vickers microhardness tester, pin-on-disc tribometer and potentiodynamic polarization tests. The results show that the thickness of plasma RE nitrocarburized layer is much thicker than that formed by nitrocarburizing without RE addition. The incorporation of RE does not change the kind of the phases and the nitrocarburized layer consists mainly of nitrogen and carbon expanded martensite （aN）, γ-Fe4N and a-Fe with a trace of CrN phases. The surface microhardness of plasma nitrocarburized layer can be increased by 100 HV after RE addition. Wear resistance of the specimen can be apparently improved by low temperature plasma nitrocarburizing with and without RE addition and without sacrificing its corrosion resistance. Wear reduction effect of low temperature plasma nitrocarburizing with RE addition is better than that of the conventional one.